The Know-Want-Learn (KWL) Strategy in English Learning of Junior High School Student: English - Aditya Ridho Fatmawan; Dwi Mahya Sari; Desty Endrawati Subroto; Nurmadina Hs; Desy Liliani Husain (Prodi Tadris Bahasa Inggris, 2023)
The aim of teaching foreign language is defined in terms of four skills. Listening, speaking, reading, and writing. It clearly shows that the purpose of teaching English is to enable students to master the four skills. The objective of this research were to know whether KWL strategy improve students’ narrative text reading ability, teachers’ performance, and students’ participation during the teaching-learning process at 27 Students eighth grade of Junior High School Student. To see the teachers’ performance and students’ participation (Teaching Learning Process), qualitative data was used (interview and observation sheet). Meanwhile, quantitative data (students’ score) was used to know students' ability to read narrative text (Learning Product). This research was conducted at Junior High School students of Gunung Labuhan Lampung. The subject of this research was students of class Eighth Grade. This research used classroom action research (CAR). The action research was done in two cycles. Each cycle was done in three meetings. Each cycle consists of planning, acting, observing, and reflecting. Based on the result of the cycles from pre-test data, students passed grade 37%, which increased in every cycle as follows, Post Cycle 1 got score students passing grade 44,4%. In Post Cycle II got score students passing grade 81,5% and from the observation sheet result, 90% were active during the teaching-learning process and 81% students gain score 70 or more. Referring to the research, it concluded that KWL strategy improved students’ narrative text reading ability, teachers’ performance and students’ participation during the teaching-learning process.